Does mood induction elicit emotion recognition biases? : an empirical study with implications for depression research - Harding, Steven (Department of Psychology, 2015)
Depression is a highly prevalent, debilitating, and sometimes-fatal mental illness. Typically, its treatment approaches are conceptualised as a dichotomy between psychological and pharmaceutical. However, a new model, in line with cogent philosophical reasoning and recent empirical evidence, integrates these approaches. The cognitive neuropsychological model places affective processing biases as central to depression aetiology and treatment-in both biological psychiatry and cognitive psychology. One affective bias, emotion recognition, is central to the tenets of this model, which, unlike some cognitive theories, places improved affective biases as temporally prior to improved mood, and as the underlying mechanism of antidepressant action. To test this account of emotion recognition bias, 103 undergraduate students participants underwent negative, positive, and neutral mood induction in a betweengroups design to assess whether mood-congruent emotion recognition biases would emerge in a multimodal (facial, vocal, musical) emotion recognition battery, while controlling for depression symptoms and assessing maladaptive cognitive schemas. Few significant emotion recognition biases resulted, but significant negative correlations between negative schemas and overall facial and musical accuracy emerged, even when controlling for depression lending some support to the cognitive neuropsychological model's premise of a bilateral relationship between schemas and emotion recognition, both of which may play a substantial role in the etiology of depression.